Association of Hepatitis B Core-Related Antigen and Antihepatitis B Core Antibody With Liver Fibrosis Evolution in Human Immunodeficiency Virus-Hepatitis B Virus Coinfected Patients During Treatment With Tenofovir. (7th June 2020) - Cruchet, Romuald; Dezanet, Lorenza N C; Maylin, Sarah; Gabassi, Audrey; Rougier, Hayette; Miailhes, Patrick; Lascoux-Combe, Caroline; Chas, Julie; Girard, Pierre-Marie; Delaugerre, Constance; Lacombe, Karine; Boyd, Anders
Abstract: Background: Quantitative hepatitis B core-related antigen (qHBcrAg) or antihepatitis B core antibody (qAnti-HBc) could be useful in monitoring liver fibrosis evolution during chronic hepatitis B virus (HBV) infection, yet it has not been assessed in human immunodeficiency virus (HIV)-HBV-coinfected patients undergoing treatment with tenofovir (TDF). Methods: One hundred fifty-four HIV-HBV-infected patients initiating a TDF-containing antiretroviral regimen were prospectively followed. The qHBcrAg and qAnti-HBc and liver fibrosis assessment were collected every 6–12 months during TDF. Hazard ratios (HRs) assessing the association between qHBcrAg/qAnti-HBc and transitions from none/mild/significant fibrosis to advanced fibrosis/cirrhosis (progression) and from advanced fibrosis/cirrhosis to none/mild/significant fibrosis (regression) were estimated using a time-homogeneous Markov model. Results: At baseline, advanced liver fibrosis/cirrhosis was observed in 40 (26%) patients. During a median follow-up of 48 months (interquartile range, 31–90), 38 transitions of progression (IR = 7/100 person-years) and 34 transitions of regression (IR = 6/100 person-years) were observed. Baseline levels of qHBcrAg and qAnti-HBc were not associated with liver fibrosis progression (adjusted-HR per log10 U/mL = 1.07, 95% confidence interval [CI] = 0.93–1.24; adjusted-HR per log10 Paul-Ehrlich-Institute [PEI] U/mL = 0.85, 95% CI = 0.70–1.04, respectively) or regression (adjusted-HR per log10 U/mL = 1.17, 95% CI = 0.95–1.46; adjusted-HR per log10 PEI U/mL = 0.97, 95% CI = 0.78–1.22, respectively) after adjusting for age, gender, duration of antiretroviral therapy, protease inhibitor-containing antiretroviral therapy, and CD4 + /CD8 + ratio. Nevertheless, changes from the previous visit of qAnti-HBc levels were associated with liver fibrosis regression (adjusted-HR per log10 PEIU/mL change = 5.46, 95% CI = 1.56–19.16). Conclusions: Baseline qHBcrAg and qAnti-HBc levels are not associated with liver fibrosis evolution in TDF-treated HIV-HBV coinfected patients. The link between changes in qAnti-HBc levels during follow-up and liver fibrosis regression merits further study. Abstract : Serum quantification of hepatitis B core-related antigen and antihepatitis B core antibodies are not associated with liver fibrosis evolution in TDF-treated HIV-HBV-coinfected patients. Our findings support the need to assess other novel HBV markers to predict this clinical outcome.